2016
DOI: 10.1016/j.jaci.2016.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously increased fraction of exhaled nitric oxide levels and blood eosinophil counts relate to increased asthma morbidity

Abstract: Background: We have previously described that fraction of exhaled nitric oxide (FENO) levels and blood eosinophil counts offer additive information in relation to asthma and asthma exacerbations when analyzing data from a large population study. Objective: We sought to investigate increased FENO levels and blood eosinophil counts in relation to lung function, bronchial hyperresponsiveness (BHR), and asthma control in a cohort of young asthmatic patients. Methods: Measurements of FENO levels and blood eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
100
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 39 publications
5
100
1
1
Order By: Relevance
“…Simultaneously elevated levels of FeNO and B‐Eos related to an impaired lung function, wheezing and wheezing during sleep last year, but not to asthma attacks. The last named finding is in contrast to previous findings in the general and asthma populations . However, singly elevated B‐Eos related to asthma attacks and symptoms leading to a healthcare contact also when adjusted for FeNO levels, in line with earlier findings from the general population and asthmatics in NHANES 2007‐10 or real‐life analysis of patients with asthma .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Simultaneously elevated levels of FeNO and B‐Eos related to an impaired lung function, wheezing and wheezing during sleep last year, but not to asthma attacks. The last named finding is in contrast to previous findings in the general and asthma populations . However, singly elevated B‐Eos related to asthma attacks and symptoms leading to a healthcare contact also when adjusted for FeNO levels, in line with earlier findings from the general population and asthmatics in NHANES 2007‐10 or real‐life analysis of patients with asthma .…”
Section: Discussionsupporting
confidence: 83%
“…Thus, FeNO and B‐Eos are both dependent on cytokines related to type 2 inflammation, but as they reflect different inflammatory pathways, these biomarkers may represent different parts of the inflammation in asthma. Previous studies on the combination of FeNO and B‐Eos were carried out in the general population and in adolescents and young adults with asthma . However, there is a lack of studies for this combination of markers in subjects with asthma of a broad age range.…”
Section: Introductionmentioning
confidence: 99%
“…Further, B‐Eos count related independently to reduced lung function and AHR. Our group has previously reported that FeNO and B‐Eos are independently associated with asthma and asthma morbidity, and that they should be used in an additive manner …”
Section: Discussionmentioning
confidence: 99%
“…Systemic components, such as blood eosinophil (B‐Eos) count, have also been used as markers of type 2 inflammation. Simultaneous measurement of FeNO and B‐Eos enables assessment of both local and systemic inflammation, and the combined use has shown additive predictive value for asthma morbidity . Type‐2 inflammation has previously been considered to be driven primarily by type 2 T helper (Th2) cells, but lately the role of the innate lymphoid cell type 2 (ILC2) in this type of inflammation has become increasingly clear.…”
Section: Introductionmentioning
confidence: 99%
“…Serum periostin was identified as a secreted product of IL-13-stimulated bronchial epithelial cells 54 , and has been closely correlated with airway eosinophilia in some 55 , but not all 56,57 , studies. Some 58,59 , but not all 57 , studies suggest a combination of biomarkers gives better prediction of clinical outcomes. Since blood eosinophils are easily accessible, show the best association with airway eosinophilia, and are predictive of treatment response, this biomarker shows great promise for the identification of the eosinophilic endotype in clinical practice.…”
Section: Barcelona Respiratory Networkmentioning
confidence: 99%